Uma abordagem para trabalho cooperativo com suporte computadorizado - Albino, João Pedro (Universidade Federal de São Carlos, 1993)
Nowadays, the modern society is going through radical technological changes that are generating debate and proposals concerning new ways of working. Information, computer and communication technologies represent an important role as modifiers of the way the work is done. When people in any kind of organization join themselves in workgroups to solve a problem or make a decision it is necessary to develop or use new dynamic group techniques for these people to work together. So, this work is concerned with matters of this kind where the computer is used to support the tasks of workgroups, what is quite new and revolucionary, being necessary some facilities to aid in the development and coordination of the work. In this dissertation it is introduced and defined this new technology. It is also presented a prototype of a groupware tool which helps people organize workshops, conferences, seminars, etc. The developed prototype brings some contributions to the CSCW área an is the begining of a more complex system to help the organization of Academic Events (conferences, workshops, etc.). From the user point of view the cooperation is seen as the possibility to the program committee, to share the decision to choose the papers that will make the technical program. In this case the decision should be centralized on-line. The tool allows that the referres can make, in assincronous mode, the assessment of the papers they are judging. Among many others tasks the tool allows the recording of the structure of the event, incluiding comittes,their chairs and participants, role definition and script of each stake holder, etc.
An approach to computer-supported cooperative work
Keywords: Trabalho cooperativo; CSCW; Cooperativismo; Sistema de apoio à decisão em grupo; Conferência computadorizada; Trabalho em grupo com suporte cooperativo; Computadores; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO